A narrative review of the role of renal artery intervention in renovascular hypertension - Che, Li; Wang, Zilong (Frontiers in Surgery, 2025)
Renovascular hypertension is a form of secondary hypertension caused by renal artery stenosis and often shows a limited response to medical treatment. Over recent years, renal artery interventions, primarily angioplasty and stenting, have been increasingly used as treatment options in selected patients. This narrative review summarizes current techniques, clinical outcomes, and evidence related to renal artery interventions in the management of renovascular disease. It also highlights existing knowledge, challenges, emerging technologies, and future directions for improving patient selection, procedural safety, and long-term effectiveness of intervention strategies. By consolidating recent developments and identifying critical knowledge gaps, this review provides an updated and practical overview for clinicians and offers guidance for future research in the field of renal artery intervention.